Factors Affecting the Adherence to Partial Enteral Nutrition Combined with the Crohn’s Disease Exclusion Diet in Crohn’s Disease Adult Patients - Vaios Svolos; Dimitra Eleftheria Strongylou; Georgios Charmantzis; Evgenia Popko; Dimitra Kanta; Christos Argyriadis; Dimitrios Grigoriou; Kalliopi Anna Poulia; Andreas Kapsoritakis; Konstantinos Argyriou; Odysseas Androutsos (Healthcare, 2026)
Background/Objectives: Enteral nutrition (EN), delivered either exclusively (EEN) or partially (PEN) in combination with the Crohn’s Disease Exclusion Diet (CDED), represents an evidence-based dietary therapy for active Crohn’s Disease (CD), recommended in clinical guidelines. However, adherence to this therapy remains suboptimal among adult patients. This study aimed to explore the intention to repeat CDED & PEN alongside perceived factors affecting adherence to CDED & PEN in CD adult patients. Methods: A single-center, cross-sectional qualitative study was conducted between October 2025 and March 2026 at a private dietetic practice in Larissa, Greece. Semi-structured interviews were undertaken and analyzed using thematic analysis. Results: Out of the 88 patients screened, 15 adults with CD participated in semi-structured interviews. Four overarching themes emerged: (1) intention to repeat CDED & PEN, with all participants reporting willingness to repeat CDED & PEN in the event of future relapse; (2) barriers to CDED & PEN adherence, including challenges in social situations involving food; (3) facilitators of CDED & PEN adherence, such as improved symptom control and increased sense of security; and (4) dual factors affecting CDED & PEN adherence, whereby meal preparation demands, taste and variety, and social and environmental support acted as either facilitators or barriers against adherence depending on individual circumstances. Conclusions: Greek adults with CD showed strong willingness to reinitiate CDED & PEN during relapse. Addressing modifiable barriers, particularly dietary monotony and financial burden, alongside strengthening structured dietitian support and personalized dietary guidance, may help optimize adherence in clinical practice.